2000
DOI: 10.1016/s1010-7940(00)00384-5
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic implications of a positive bronchial resection margin

Abstract: Prognosis of peribronchial infiltration is similar to N2 disease. In situ carcinoma does not influence survival per se. Local control of disease is probably in part due to radiotherapy. However, the high prevalence of unrelated late deaths suggests an adverse impact of radiotherapy on survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
60
1
3

Year Published

2003
2003
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(64 citation statements)
references
References 21 publications
0
60
1
3
Order By: Relevance
“…20 Many but not all studies of positive margins of surgically treated lung cancers have shown adverse impact by residual disease. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16] Microscopic residual tumor at the bronchial resection margin has then been divided into different patterns. Cotton 1 first divided microscopic residual disease into mucosal tumor (spreading from a mucosal lesion), and extramucosal microscopic residual disease (tumor involving peribronchial soft tissues or tumor within lymphatics).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…20 Many but not all studies of positive margins of surgically treated lung cancers have shown adverse impact by residual disease. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16] Microscopic residual tumor at the bronchial resection margin has then been divided into different patterns. Cotton 1 first divided microscopic residual disease into mucosal tumor (spreading from a mucosal lesion), and extramucosal microscopic residual disease (tumor involving peribronchial soft tissues or tumor within lymphatics).…”
Section: Discussionmentioning
confidence: 99%
“…As described above, outcomes vary with site of positive margins, with submucosal, peribronchial and lymphatic space involvement at margins found to be worse than mucosal positive margins in most studies. 6,7,9,16,17,23 Several studies have found little benefit from postoperative radiation therapy. 3,5 Chemotherapy added to radiation therapy may add additional benefit in some series.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…If positive marginal oncogenic cellswere found, the patients were subjected to additional surgery, hyperactive anxiety and discomfort [2][3][4][5]. There for it is becoming an indispensable need to analysis oncogenes in molecular labels by incorporating cancer specific biomarkers to improve cancer identification and screening.…”
Section: Introductionmentioning
confidence: 99%